Training within industry - Kuhns, Susan; Bollinger, Steven R. (Manufacturing insights (DVD), 2009)
Shows how the four modules of TWI: Job relations (JR), Job instruction (JI), Job methods (JM) and Job safety (JS) work together to sustain lean manuacturing. Together, they generate cooperation and positive employee relations, teach supervisors how to quickly train employees to do a job correctly, establish and maintain standardized work, provide a framework for sustained continuous process improvement, and maintain a safe work environment.